2022
DOI: 10.1111/ajt.16861
|View full text |Cite
|
Sign up to set email alerts
|

Genetically targeting the BATF family transcription factors BATF and BATF3 in the mouse abrogates effector T cell activities and enables long-term heart allograft survival

Abstract: T cells must be activated and become effectors first before executing allograft rejection, a process that is regulated by diverse signals and transcription factors. In this study, we studied the basic leucine zipper ATF‐like transcription factor (BATF) family members in regulating T cell activities in a heart transplant model and found that mice deficient for both BATF and BATF3 (Batf−/−Batf3−/− mice) spontaneously accept the heart allografts long‐term without tolerizing therapies. Similarly, adoptive transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In the setting of infections, the impaired effector differentiation and function of BATF-deficient CD8 + T cells eventually results in the defeats to eliminate lymphocytic choriomeningitis virus (LCMV) infections ( 24 , 31 , 32 ). The requirement of BATF family transcription factors in effector differentiation is also demonstrated in other settings ( 40 42 ). Consistent with these findings, our data showed that BATF-deficient CD8 + T cells exhibited a compromised effector phenotype and lost the capacity to mediate transplant rejection.…”
Section: Discussionmentioning
confidence: 69%
“…In the setting of infections, the impaired effector differentiation and function of BATF-deficient CD8 + T cells eventually results in the defeats to eliminate lymphocytic choriomeningitis virus (LCMV) infections ( 24 , 31 , 32 ). The requirement of BATF family transcription factors in effector differentiation is also demonstrated in other settings ( 40 42 ). Consistent with these findings, our data showed that BATF-deficient CD8 + T cells exhibited a compromised effector phenotype and lost the capacity to mediate transplant rejection.…”
Section: Discussionmentioning
confidence: 69%
“…One studies have shown that after in vitro and in vivo injection of endotoxin and LPS, six candidate genes(BATF, BID, C3aR1, IL1RN, SEC61B and SLC43A3) were identi ed to be associated with in ammation and atherosclerosis [28] . Another study demonstrate that the BATF and BATF3 are critical regulators of T effector functions, thus making them attractive targets for therapeutic interventions in heart allograft [29] . Our Xcell results showed that the number of macrophages in unstable plates increased signi cantly, indicating that the number and function of macrophages play a very important role in the progression of plaques, above studies indicate that BATF is mainly involved in the progression of cardiovascular disease as a regulatory factor of T cells, a single-cell sequencing database analysis showed that (https://panglaodb.se/index.html) BATF was also highly expressed in macrophages, so, it may be involved in regulating plaque instability or rupture.…”
Section: Discussionmentioning
confidence: 99%
“…One studies have shown that after in vitro and in vivo injection of endotoxin and LPS, six candidate genes (BATF, BID, C3aR1, IL1RN, SEC61B and SLC43A3) were identified to be associated with inflammation and atherosclerosis [28]. Another study demonstrate that the BATF and BATF3 are critical regulators of T effector functions, thus making them attractive targets for therapeutic interventions in heart allograft [29]. Our xCell results showed that the number of macrophages in unstable plates increased significantly, indicating that the number and function of macrophages play a very important role in the progression of plaques, above studies indicate that BATF is mainly involved in the progression of cardiovascular disease as a regulatory factor of T cells, a single-cell sequencing database analysis showed that (https:// pangl aodb.…”
Section: Discussionmentioning
confidence: 99%